Prevalence of gastrointestinal parasitism of cattle in Banskhali upazilla, Chittagong, Bangladesh (Journal of Advanced Veterinary and Animal Research, 2015)
The  objectives  of  this  study  were  to  investigate  the prevalence of gastrointestinal parasitism (GP), and to determine  the  effects  of  age,  sex,  breed,  body  score and body weight in the occurrences of GP of cattle in Banskhali  Upazilla,  Chittagong,  Bangladesh.  A  total of 50 fecal samples were randomly collected directly from rectum of cattle. The samples were examined by routine  coproscopical  methods  for  the  presence  of different parasites and oocysts. Overall prevalence of GP  infestation  was  72%  (n=36/50).  Prevalence  of Paramphistomum  spp.  infestation  was  found  to  be the highest (30%; n=15/50) followed by Toxocara spp. (12%;  n=6/50),  Fasciola  spp.  (10%;  n=5/50), Oesophagostomum  spp.  (8%;  n=4/50),  Moniezia  spp. (6%;  n=3/50)  and  Trichostrongylus  spp.  (2%;  n=1/50). Young  cattle  were  mostly  infested  as  compared  to adult and calf. The results of this study provides an epidemiological  forecast  showing  the  prevalence  of GP in cattle, which can be helpful for the clinician in diagnosis of such infections.http://dx.doi.org/10.5455/javar.2015.b113